Risk factors for colorectal cancer in Morocco: A systematic review - Lahoucine Amsdar; Abderrahman Arechkik; Abdelaaziz Touaddi; Mohammed Akrim; Laila Lahlou; Mehdi Soufi (Elsevier, 2024)
Background: This systematic review focuses on detecting the main risk factors for colorectal cancer in Morocco. Methods: The study was conducted according to the recommendations of the "Preferred Reporting Items for Systematic Reviews and Meta-Analyses". The systematic search included studies published between 2010 and 2022. PubMed, ScienceDirect and Google Scholar databases were used for data collection. Prior to conducting this study, the research protocol was registered on the PROSPERO registry (CRD42023423796). To measure association strengths we used Odds Ratios, 95 % confidence intervals and P-values if they exist. Results: The results revealed that out of 9173 records initially identified, 17 records were included in the present systematic review. The main non-modifiable risk factors associated with colorectal cancer were family history of colorectal cancer and family history of other cancers (p ≤ 0.001). Modifiable risk factors include common smoking [OR, 2.18; 95 % CI, 1.37-3.48], excess consumption of red meat (>3 times/week) [OR, 4.4; 95 % CI, 1.6-11.9; p, 0.0001]. Similarly, the consumption of more than 62.93 g/day of processed red meats (p = 0.001). In addition, consumption of sausages and cream pastry exceeding three times a day was significantly associated with colorectal cancer [OR, 5.7; 95 % CI, 1.2-27.7; p, 0.0001 and OR, 3.9; 95 % CI, 1.2-12.5; p, 0.001] respectively. Yet, alcoholic beverages were potential risk factors [OR, 0.98; 95 % CI, 0.46-1.48]. Modern dairy products [OR, 0.81; 95 % CI, 0.2-0.91] and traditional dairy products have a protective role [OR, 0.81; 95 % CI, 0.72-0.90]. Conclusion: The results of this systematic review indicate that consumption habits of red meats, processed meats and cream pastry are the main risk factors for colorectal cancer in Morocco. Thus, to reduce its prevalence, in-depth research is essential to effectively guide prevention strategies and approaches based on changing risk behaviors.